Getting the (Gender-Disaggregated) Lay of the Land : Impact of Survey Respondent Selection on Measuring Land Ownership and Rights - Kilic, Talip; Moylan, Heather; Koolwal, Gayatri (World Bank, Washington, DC, 2020)
Foundational to the monitoring of international goals on land ownership and rights are the household survey respondents who provide the required individual-disaggregated data. Leveraging two national surveys in Malawi that differed in their approach to respondent selection, this study shows that, compared with the international best practice of privately interviewing adults about their personal asset ownership and rights, the business-as-usual approach of interviewing the most knowledgeable household member(s) on adult household members’ ownership of and rights to assets leads to (i) higher rates of exclusive reported and economic ownership of agricultural land among men, and (ii) lower rates of joint reported and economic ownership among women. Further, substantial agreement exists on agricultural landowners and rights holders, as reported by the privately-interviewed spouses. When discrepancies emerge, proxies for greater household status for women are positively associated with the scenarios where women attribute at least some land ownership to themselves.